2014
DOI: 10.1177/0265407514523552
|View full text |Cite
|
Sign up to set email alerts
|

How does love magic work? The regulation of closeness and affect by magical thinking

Abstract: Sympathetic magic and attachment theory enable the drawing of a parallel between functions of material possessions that are used in the absence of parents and a romantic partner. The ascribing of magical significance to objects may be a coping strategy facilitated by dispositional anxieties and situational threats. The aim of this research was to examine whether romantic magical thinking (MT) comforts individuals by regulating the perceived distance from a loved one. Study 1 confirmed that perceived closeness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 60 publications
(106 reference statements)
4
11
0
2
Order By: Relevance
“…We showed that romantic SM may depend on two relatively independent factors: a cognitive vulnerability to accept magical intuitions manifested by increased experiential information processing (Study 1 and 2), and motivation to increase closeness in a romantic relationship indicated by both increased attachment anxiety and decreased attachment avoidance (Studies 1, 2, and 3). Regarding motivational factors, our results corroborate earlier findings (Niemyjska 2015;Niemyjska et al 2011) showing that romantic SM is related to the increased perception of a partner's closeness. However, this research also extends previous work by showing that romantic SM has two relatively independent sources.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…We showed that romantic SM may depend on two relatively independent factors: a cognitive vulnerability to accept magical intuitions manifested by increased experiential information processing (Study 1 and 2), and motivation to increase closeness in a romantic relationship indicated by both increased attachment anxiety and decreased attachment avoidance (Studies 1, 2, and 3). Regarding motivational factors, our results corroborate earlier findings (Niemyjska 2015;Niemyjska et al 2011) showing that romantic SM is related to the increased perception of a partner's closeness. However, this research also extends previous work by showing that romantic SM has two relatively independent sources.…”
Section: Discussionsupporting
confidence: 90%
“…Factor Structure of RSMS On the basis of observations reported in the literature (e.g., Belk and Coon 1993;Frost and Steketee 2011;Miller 2008), we have assumed that due to a similar function for adults, that is, regulation of perceived closeness to a loved one (for a discussion on this topic, see Niemyjska 2015), both laws of SM operate together. Therefore, we expected a unidimensional structure of the RSMS.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations